A novel three-dimensional orthogonal star honeycomb structure with negative Poisson’s ratio - He, Baofeng; Huang, Qian; Shi, Zhaoyao (Engineering Research Express, 2024)
A novel three-dimensional(3D) orthogonal star honeycomb structure with increased strength and negative Poisson’s ratio(NPR) performance that is not subject to angle constraints was proposed, and the calculation model of Young’s modulus and Poisson’s ratio of the cell structure under axial load was derived in this study. Through the investigation of the deformation mode and the finite element (FE) research results of the structure, it is found that the longitudinal length parameter l 2 and angle parameter θ 2 are important concave axes that affect the mechanical properties of materials. The quasi-static compression experimental results shows that the constraints of adjacent elements can enhance the strength of the structure to a certain extent, and the theoretical analysis results and the FE simulation results were in good agreement with the experimental results. In addition, the results are also concluded that the prediction of Young’s modulus and Poisson’s ratio and the designability of mechanical properties of 3D orthogonal star honeycomb structures could be achieved by the theoretical calculation formula derived in this study.